Performance of segmentation in infrared breast thermograms using level set method - Saran Raj, S; R, Hariharan (International Journal of Engineering and Technology, 2018)
Breast cancer is the overall most basic obtrusive tumour in females. The breast cancer can be dealt with successfully that they are analyzed at a beginning time. It can watch the principal indication of shaping up disease before mammography can recognize. The thermal data can be appeared in a pseudo shading where each shading speaks to a particular scope of temperature. Different techniques can be connected to extricate hot districts for distinguishing associated areas with interests in the thermograms and possibly suspicious tissues. in this paper at first the pre process of the thermogram pictures are done then they are improved. The upgraded pictures are divided by two picture segmentation strategy: K-means and level set technique are study and compared. The highlights have been extracted and classification for both the segmentation techniques.